Exploring Critical Pedagogy in an Indonesian Higher Education: Possibilities and Challenges - Wulandari Santoso (Universitas PGRI Yogyakarta, 2021)
The prior and recent literature on the second and foreign language education has touched upon a number of discussion regarding Critical Pedagogy (CP). CP is generally defined as an approach to teaching and curriculum that seeks to understand and the historical and socio-political context of schooling and pedagogical practices that aim not only to change the schooling, but also the wider society. This case study aimed to investigate the perspective of teachers towards CP in an Indonesian higher education in order to see the possibilities and the challenges of applying CP in this particular context. Semi-structured interviews were used to collect data to five teachers, and the data was analysed using a thematic analysis. The result of this study revealed that while some of the teachers were in favour of implementing CP, the others seemed to be rather pessimistic due to some constraints they had in the classroom. Some strategies, e.g. problem posing techniques were found to be essential to engage the students in critical dialogue with the teachers. It is hoped that this research can shed new light on to what extent CP can be implemented in certain educational contexts and on possible challenges that teachers may face in the process.Â